Magnesium‐containing layered double hydroxides as orthopaedic implant coating materials—An in vitro and in vivo study. Issue 3 (1st May 2015) - Weizbauer, Andreas; Kieke, Marc; Rahim, Muhammad Imran; Angrisani, Gian Luigi; Willbold, Elmar; Diekmann, Julia; Flörkemeier, Thilo; Windhagen, Henning; Müller, Peter Paul; Behrens, Peter; Budde, Stefan
Abstract: The total hip arthroplasty is one of the most common artificial joint replacement procedures. Several different surface coatings have been shown to improve implant fixation by facilitating bone ingrowth and consequently enhancing the longevity of uncemented orthopaedic hip prostheses. In the present study, two different layered double hydroxides (LDHs), Mg‐Fe‐ and Mg‐Al‐LDH, were investigated as potential magnesium (Mg)‐containing coating materials for orthopaedic applications in comparison to Mg hydroxide (Mg(OH)2 ). In vitro direct cell compatibility tests were carried out using the murine fibroblast cell line NIH 3T3 and the mouse osteosarcoma cell line MG 63. The host response of bone tissue was evaluated in in vivo experiments with nine rabbits. Two cylindrical pellets (3 × 3 mm) were implanted into each femoral condyle of the left hind leg. The samples were analyzed histologically and with μ‐computed tomography (μ‐CT) 6 weeks after surgery. An in vitro cytotoxicity test determined that more cells grew on the LDH pellets than on the Mg(OH)2 ‐pellets. The pH value and the Mg 2+ content of the cell culture media were increased after incubation of the cells on the degradable samples. The in vivo tests demonstrated the formation of fibrous capsules around Mg(OH)2 and Mg‐Fe‐LDH. In contrast, the host response of the Mg‐Al‐LDH samples indicated that this Mg‐containing biomaterial is a potential candidate for implant coating. © 2015 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 104B: 525–531, 2016.